Dressing an existential wound (DEW) – a new model for long‐term care following disasters. Issue 3 (3rd December 2015) - Rehnsfeldt, Arne; Arman, Maria
Abstract : Background: Presence, concern, compassion and universal or ontological unity between human beings have emerged as crucial to the healthy development of people who have experienced disasters. Aim and objectives: The aim of this article was to present a new model for long‐term care following disasters. The objective of the model was to contribute to the readiness for long‐term care following disasters in professionals and nonprofessionals as a result of their understanding of the model. Design: A longitudinal qualitative study of Swedish tourists affected by the South East Asian tsunami in 2004 is the empirical base for this clinical model, which was developed within the framework of caring science. Methods: A hermeneutic method was used. Results: The model is based on the assumption that life issues are an important aspect of long‐term follow‐up after a disaster. The term 'life issues' refers to the following: existential questioning of life's content, values and priorities; people's relationships with each other; and the importance of health, suffering, love and death. Life issues also refer to the way in which survivors form a new understanding of life after a disaster experience. Existential care is based on a charitable attitude of compassion and mercy towards one's fellows, be they professionals, families or wider society. By presenting eight theses, the model provides an approach based on compassion that works as an existential dressing for survivors of disaster. Conclusions: The model gives a knowledge base and approach for the long‐term care of survivors, including practical advice.